Predicting density distribution in green compacts using finite element simulations - Hrairi, Meftah; Chtourou, Hedi (2010)
Finite element simulation of the rigid die compaction of metal powders can significantly help designers avoid some of the typical problems they face such as the high density gradients within compacted parts and related cracking. In this paper, the modeling of an axisymmetric flanged part using finite element packages ABAQUS and LS-DYNA has been investigated. A material constitutive model of the Cap type, that allows the use of variable elasticity as well as a density dependent Cap aspect ratio, has been implemented into the finite element code ABAQUS whereas the geological Cap model in its conventional form was implemented in the finite element code LS-DYNA. The effect of density distribution in the part was analyzed through the plastic strain that was generated. The results obtained from the two softwares were compared to the experimental density map and a good agreement has been noted.